PHYSICAL EDUCATION IN SCHOOLS OF PUBLIC HEALTH PROMOTION (Fiep Bulletin - online, 2013)
The Scholar Physical Education (SPE) has been extensively targeted for discussion about its social role in order to support his importance as a compulsory subject  and its importance in society. Researchers from the area of education, as Armstrong and Sleap (1990), admit that the school, through physical education has an important role to play, whereas the Physical Education working human movement, an important factor in the process of acquisition and maintenance of health. The purpose of this article is to stimulate reflection on how the SPE can influence and benefit the health of the population. The methodology used in this study was a literature review, descriptive in nature, drawn from papers already published, consisting mainly of books and articles from periodicals that address issues and relations between the Health Promotion and Physical Education. It was verified through this study, the strong relationship between physical inactivity in childhood and adolescence and sedentary lifestyle in adulthood and this affinity worries us because of diseases that can arise due to lack of physical activity practice. Is important the understanding that health is gained through changes in attitudes and habits of the daily lifestyle of children and adolescents, since the habits relating to promotion of health should be cultivated throughout life and not just used for a particular purpose momentary. We conclude the importance of physical education in health promotion, which is meant beyond the physical walls and school age, making him a valuable social tool.
Keywords: Physical education in school; public health; promotion of health.